2000
DOI: 10.1111/j.1745-4522.2000.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Quality of Frying Oil and Oil Extracted From Potato Fritters Fried in Liquid and Partially Hydrogenated Rapeseed Oils

Abstract: The increase in consumption of food fried in the so‐called ‘deep‐frying‐oil’entails the necessity of knowledge of both thermooxidative transformation occuring in the frying medium and chemical composition of oil absorbed by the fried product. The aim of this study was to correlate the quality of frying medium and oil extracted from potato fritters fried under rigorously controlled laboratory conditions in liquid and partially hydrogenated rapeseed oils. Oxidation and polymerization reactions predominated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Other authors also report a linear increase in FFA content with frying time in different frying media. Hazuka et al 4 observed higher acid value in hydrogenated rapeseed oil as compared with liquid oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also report a linear increase in FFA content with frying time in different frying media. Hazuka et al 4 observed higher acid value in hydrogenated rapeseed oil as compared with liquid oil.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the content of fatty acids in the samples, defined as a loss (L 18:X ), in relation to the initial oil content was related to the total content of C16:0 and C18:0 fatty acids. 4 The content of polar fraction was determined according to AOAC standards. 22 Soxhlet's method was used for determining fat content of French fries.…”
Section: Methodsmentioning
confidence: 99%
“…The second calibration model was established using the reflectance within the feature wavelength ranges [16]. With the similar procedures of previous calibrations, the crossvalidation results for predicting acid value, viscosity, and TPC for three types of oil samples are shown in Figs.…”
Section: Model 1: Calibration Model Using a Spectralmentioning
confidence: 99%
“…Hazuka and colleagues showed that oil extracted from potato fritters deep fried in cooking oil that was used over 1-5 day of frying, as often done in restaurants, contained PV of 10.3 - 11.5 mEq O 2 /kg of extracted oil and AV of 103 - 184. 73 Thus, the oil used to provide LOPs in our study is in the ballpark for representing LOPs level from human fast-food item such as potato fries or fritters, although the PV (28.68 mEq O 2 /kg) was higher while AV (45.13) was lower in our LOPs source. Another study found that oil extracted from fried potatoes contained approximately 536 mg/L of HNE in the oil, 74 in contrast to the lower 15.0 mg/L of HNE in our LOPs source.…”
Section: Discussionmentioning
confidence: 90%